Graduate satisfaction: how experiential learning supercharges employability skills / Wisudani Rahmaningtyas ... [et al.] - Rahmaningtyas, Wisudani; Joyoatmojo, Soetarno; Sulistyaningrum Indrawati, Cicilia Dyah; -, Tri Murwaningsih (Universiti Teknologi MARA, 2025)
The low absorption of university graduates into the labor market is a crucial issue that must be addressed, with many graduates experiencing a mismatch between their expertise and the job roles they choose. The aim of this study is to investigate the mediating role of employability skills in examining the effect of experiential learning on graduate learning satisfaction. This study uses a quantitative approach. Data were collected from 297 graduates of the Office Administration Education Study Program in Central Java via an online questionnaire using a 1-5 Likert scale. Data analysis was conducted using Structural Equation Modeling (SEM) with the warpPLS software, including validity testing, collinearity, and the relationships between variables through path coefficients. The research results support all hypotheses, showing a significant positive relationship between employability skills and graduate learning satisfaction, experiential learning and employability skills, experiential learning and graduate learning satisfaction through employability skills. The findings conclude that employability skills successfully mediate the impact of experiential learning on graduate learning satisfaction. It is recommended that educational institutions strengthen the implementation of experiential learning opportunities, such as internships and work integrated learning, to better meet the expectations of local industries and improve students' employability skills.